Strategi Manajemen Bisnis Syariah untuk Meningkatkan Daya Saing Produk UMKM Halal: Studi Kasus di Kecamatan Gunung Tanjung, Tasikmalaya - Permana, Deni (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
The global halal industry is experiencing rapid growth with a market value reaching 2.3 trillion US dollars, providing strategic opportunities for Indonesian halal MSMEs. However, the competitiveness of halal MSMEs still faces challenges in management, certification, and market access. This study aims to examine the implementation of sharia business management strategies to enhance the competitiveness of halal MSME products in Gunung Tanjung District, Tasikmalaya Regency. The research employs a qualitative approach with a case study method involving ten halal MSME entrepreneurs, five MSME supervisors from related agencies, and three local community leaders. Data collection was conducted through in-depth interviews, participatory observations, and documentation analysis during July-December 2024. Data analysis utilized Miles and Huberman's interactive model with a thematic analysis approach. The research findings reveal that the application of sharia business management principles including honesty in business transactions, fairness in profit distribution, social responsibility toward the environment, and exemplary leadership in business operations contributes significantly to strengthening consumer trust, improving operational efficiency, and ensuring long-term business sustainability. Local community support through religious study networks and collaborative business groups, along with institutional facilitation from local government and Islamic microfinance institutions, also plays a vital role in promoting and maintaining management practices aligned with Islamic principles. Research findings demonstrate that MSMEs consistently implementing sharia business management experienced up to 75% increase in customer loyalty, 40% expansion in market reach, and an average 30% improvement in profitability compared to the period before systematic implementation of sharia principles. This research has strategic implications for the necessity of continuous capacity building and integration of Islamic values into MSME entrepreneurship training programs to strengthen the local halal economic sector and contribute to national sharia economic development.